Moderation and Tolerance in the Qur’anic Context: Significance and Analogues — A Comparative Thematic Study - Abdullah, Mustaffa Bin; Abu-Alhaj, Thabet Ahmad Abdullah; AL-Jassim, Mohammed Jassim (Journal of Cultural Analysis and Social Change, 2026)
This study examines the concepts of moderation and tolerance in the Qur'anic context, focusing on their semantic dimensions and conceptual analogues. It addresses the ambiguity surrounding these terms in contemporary Islamic discourse and their influence by Western epistemological frameworks. The research proposes Qur'anic alternatives—wasatiyyah (centrality/balance) and birr (righteousness/benevolence)—as more precise and comprehensive expressions. Using comparative and thematic methodologies, the study analyzes the linguistic, conceptual, and functional dimensions of these terms, exploring historical and contemporary applications while addressing current challenges. The findings indicate that Qur'anic concepts offer an integrated, monotheism-centered model capable of providing a balanced civilizational framework that preserves essential constants while accommodating societal and cultural variables.